Global burden of major chronic respiratory diseases among older adults aged 55 and above from 1990 to 2021: Changes, challenges, and predictions amid the pandemic - Anran Xu; Yinqin Liu; Shaobin Li; Chengyan Zhan; Yanqi Cheng; Chen Zhang; Hong Fang; Donghua Zhou (PLoS ONE, 2025)
Objective To characterize sex- and age-specific changes in the comprehensive burden of major chronic respiratory diseases (CRDs) and their attributable risk factors among adults aged ≥55 years globally, regionally, and nationally from 1990 to 2021 using the Global Burden of Disease (GBD) 2021 database. Methods Utilizing the GBD 2021 database, we performed in-depth analyses and preliminary projections of global, regional, and national burden trends for chronic obstructive pulmonary disease (COPD), asthma, and interstitial lung disease & pulmonary sarcoidosis (ILD&PS) through multi-model approaches including but not limited to Age-Period-Cohort (APC) models, Joinpoint regression, and Bayesian Age-Period-Cohort (BAPC) modeling. Results The overall global CRD burden among adults ≥55 years declined from 1990 to 2021. However, the Corona Virus Disease 2019 (COVID-19) pandemic differentially altered asthma and COPD prevalence and incidence trends globally: low Socio-demographic Index (SDI) regions experienced an accelerated increase in prevalence, while high SDI regions showed a steeper rise in incidence. High mortality and disability-adjusted life years (DALYs) rates remained concentrated in low-middle SDI regions, notably Asia and North America. Consequently, prevalent CRD cases in this age group reached 223 million (95% UI 206.5–241.5) in 2021—accounting for half of all-age cases—with 18.47 million incident cases (95% UI 16.97–20.11), causing 4.15 million deaths (95% UI 3.76–4.58) and 83.67 million DALYs (95% UI 77.49–90.36). Air pollution, smoking, obesity, and chronic cold exposure persistently influenced COPD and asthma prevalence across regions and sexes. Conclusion The pandemic shifted global CRD burden trends, particularly for asthma followed by COPD. Concurrent with global aging, burden trajectories across SDI levels raise concerns. As COVID-19 becomes endemic, older adults will experience impacts from recurrent viral infections, increasingly manifesting in coming years.